Application on local discrete expansion - M. E. Abd El-Monsef; A. M. Kozae; A. A. Abo Khadra (International Journal of Mathematics and Mathematical Sciences)
The process of changing a topology by some types of its local discrete expansion preserves s-closeness, S-closeness, semi-compactness, semi-Ti, semi-Ri, i∈{0,1,2}, and extremely disconnectness. Via some other forms of such above replacements one can have topologies which satisfy separation axioms the original topology does not have.